2014
DOI: 10.1093/jxb/eru097
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal versus diurnal CO2 uptake: how flexible is Agave angustifolia?

Abstract: SummaryIn young and mature plants of the CAM species Agave angustifolia, the day/night pattern of CO2 exchange was highly conserved under a range of environmental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…It was reported that the obligate CAM plant, Agave deserti, could switch from a strong CAM type to a C 3 type pattern when plants were watered extensively (Hartsock and Nobel 1976). However, the day/night pattern of CO 2 exchange in the obligate CAM plant, A. angustifolia, did not shift towards the C 3 pattern completely when the supply of water was effectively unlimited (Winter et al 2014 (4:006:00 h), respectively. We also consider this the phenomenon of "CAM idling".…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the obligate CAM plant, Agave deserti, could switch from a strong CAM type to a C 3 type pattern when plants were watered extensively (Hartsock and Nobel 1976). However, the day/night pattern of CO 2 exchange in the obligate CAM plant, A. angustifolia, did not shift towards the C 3 pattern completely when the supply of water was effectively unlimited (Winter et al 2014 (4:006:00 h), respectively. We also consider this the phenomenon of "CAM idling".…”
Section: Discussionmentioning
confidence: 99%
“…Esto concuerda con los datos experimentales de este y otros agaves que demuestran que la radiación fotosintéticamen-te activa, junto con el agua, es uno de los principales factores limitantes de las tasas fotosintéticas en individuos juveniles y adultos (Winter et al, 2014).…”
Section: Discussionunclassified
“…Many species of Agave are known to open stomata at night favoring CO 2 capture and minimizing water loss through transpiration . In addition, studies of photosynthesis‐related CO 2 assimilation in Agave have found that CO 2 exchange can be affected by temperature, drought, and CO 2 enrichment . There is evidence of stress by drought having effects on some quantitative characteristics of plants from several species of Agave .…”
Section: Drought and High‐temperature Avoidance Of Agave Lmentioning
confidence: 99%
“…Such physiological behavior is stimulated by CO 2 enrichment (800 ppm) during the night. At CO 2 concentrations of 800 ppm, fixation in A. angustifolia increases by 62% relative to values of CO 2 fixed at concentrations of 200 and 400 ppm . In addition, at values from −2.37 to −1.72 MPa, A. deserti and A. tequilana “Azul” lower their hydraulic conductivity ( K h ) by 50% in periods of 2 and 12 h at a temperature of 35°C, respectively.…”
Section: Drought and High‐temperature Avoidance Of Agave Lmentioning
confidence: 99%
See 1 more Smart Citation